2018
DOI: 10.4236/aim.2018.87034
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Hot Water Extracts of the <i>Paecilomyces hepiali </i>and <i>Cordyceps militaris</i> Mycelia on the Growth of Gastrointestinal Bacteria

Abstract: The gastrointestinal health is very important aspect concerning human health. It refers to nutrient and vitamin absorption, food digestion and various infectious diseases. The Paecilomyces hepiali and Cordyceps militaris are highly enriched with cordycepin and ergosterol which are considered as anti bacterial substances. Present study finds out comparative effect of hot water extract of particular fungal material on growth of six species of gastrointestinal bacteria that belong to both aerobic and anaerobic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The greatest contributor for taste-related compounds from the CM mushroom are believed to be from the 5'-AMP, soluble sugars, free amino acids, and volatile compounds [56]. In addition, the abundant monosodium glutamate-like amino acid in the CM mushroom [57] may have also contributed to the umami taste, as was also found in our previous study. Cordyceps militaris mushroom extract: bromelain:flavorzyme before retorting.…”
Section: Free Amino Acid Contentssupporting
confidence: 75%
“…The greatest contributor for taste-related compounds from the CM mushroom are believed to be from the 5'-AMP, soluble sugars, free amino acids, and volatile compounds [56]. In addition, the abundant monosodium glutamate-like amino acid in the CM mushroom [57] may have also contributed to the umami taste, as was also found in our previous study. Cordyceps militaris mushroom extract: bromelain:flavorzyme before retorting.…”
Section: Free Amino Acid Contentssupporting
confidence: 75%
“…The expected mechanism is that exogenous AMP, which penetrates into the meat muscle was not completely converted into IMP and remain unchanged from a state of AMP residue. AMP is one of the major bioactive compounds within the C. militaris mushroom with a broad range of pharmacological functions ( Gamage et al, 2018 ). Through adenosine monophosphate deaminase (AMPD) pathway, AMP could be converted into ammonia and IMP with the rate of convertion is depend on various factors including heat ( Wang et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, significant changes in the mouse gut microbiome were observed after feeding mice a major metabolite of C. militaris cordycepin [ 76 ]. Gamage and coworkers [ 77 ] showed that С. militaris water extracts exhibited different levels of inhibition of various gram-positive and gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%